Understanding the extraction of pectin from food waste - Mao, Yujie (2020)
Food waste of multi tonne scale every year is wasted throughout the food supply chain (FSC) from initial agricultural production down to final household consumption or food manufacturing industries. According to the Food and Agriculture Organization of the United Nations (FAO) data, approximately 1.3 billion tones of food (that is roughly one-third of total food produced for human comsuption) is wasted globally (Gustavsson et al., 2011); and in example of the European Union, just under 90 million tonnes of food is wasted each year, 38% of which is directly produced by the food manufacturing sector (Commission, 2010). Therefore, the need to both avoid waste and find new renewable resources has led to a new and promising research avenue: the use of food supply chain waste (FSCW) as a renewable biorefinery feedstock for valorised chemicals production (Pfaltzgraff et al., 2013).